Reversible propofol resistance in a pediatric patient with chemotherapy-induced hypertriglyceridemia: a case report - Rovner, Brooke; Greenlaw, Sydney; Ferrante, Christopher; Eason, Ashley C.; Heine, Christopher; McCoy, Nicole C. (Frontiers in Anesthesiology, 2025)
We report the case of a 10-year-old girl with high-risk B-cell acute lymphoblastic leukemia who exhibited transient resistance to propofol. While being treated with calaspargase pegol and dexamethasone during induction chemotherapy, she was found to have milky-appearing serum and bone marrow aspirate as well as markedly elevated triglycerides. Despite previously normal anesthetic responses, the patient required a markedly increased propofol dose (28 mg/kg)—over five times the range of her previous anesthetics (4.5–5.2 mg/kg)—to achieve adequate sedation for her bone marrow aspiration and biopsy. Ultimately, normal propofol sensitivity returned after triglyceride normalization. This case highlights chemotherapy-induced hypertriglyceridemia as a reversible cause of anesthetic resistance and emphasizes the importance of considering lipid levels when an unusual response to routine anesthetic administration occurs.